Mathematische Modelle in der Biologie: 2.12. bis 8.12.1984 - Hadeler, Karl-Peter; Jäger, Willi (Tagungsbericht, 1984)
Wolfgang Alt, Heidelberg; W. Börsch-Supan, Mainz; Erich Bohl, Konstanz; Stavros Busenberg, Claremont; Vincenzo Capasso, Bare; Kenneth L. Cooke, Claremot; Odo Diekmann, Amsterdam; Witta Ebel, Tübingen; J. P. Gabriel, Fribourg; Michael R. Guevara, Amsterdam; Mats Gyllenberg, Amsterdam; K. P. Hadeler, Tübingen; Uwe an der Heiden, Bremen; Herbert W. Hethcote, Iowa City; Josef Hofbauer, Wien; Frank C. Hoppensteadt, Utha; W. Jäger, Heidelberg; Simon A. Levin, Ithaca; Michael C. Mackey, Montreal; Mario Markus, Dortmund; J. A. J. Metz, Leiden; Masayasu Mimura, Hiroshima; Piero de Mottoni, Rom; R. M. Nisbet, Glasgow; Yasumasa Nishiura, Kyoto; H. E. Nusse, Utrecht; P. R. Parthasarathy, Tübingen; O. Rössler, Tübingen; Franz Rothe, Tübingen; Renate Schaaf, Heidelberg; Michelle Schatzmann, Palaiseau; Dieter Schenzle, Tübingen; K. Schilling, Bayreuth; Konrad Schumacher, Heidelberg; Horst Thieme, Amsterdam; Paul Waltman, Iowa City
Abstracts engl
Keywords: Konferenzschrift